Law, land use and the environment: Afro-Indian dialogues - Christoph Eberhard (Institut Français de Pondichéry, 2008)
Our present is characterized by a heretofore unknown pressure on the environment, raising our awareness of the fragility of our planet and our responsibility to preserve it. How to reconcile this exigency with the challenge of demographic explosion? How to ensure a use of natural resources for human wellbeing that is not entirely dictated by market forces? How to rethink the relation between man and land and the environment? The terms 'governance' and 'sustainable development' contribute to a reshaping of the Law that is aimed at articulating contemporary political, social, economic and environmental issues. The focus of this book is on the major stakes involved and on the way to elaborate possible modes of thought and action through the exploration of African and Indian situations by means of an interdisciplinary and intercultural approach. By promoting a 'South - South' dialogue, it also decenters global reflections that continue to be largely dominated by the 'North'.